2018
DOI: 10.1038/s41467-018-03315-8
|View full text |Cite
|
Sign up to set email alerts
|

Chiral DOTA chelators as an improved platform for biomedical imaging and therapy applications

Abstract: Despite established clinical utilisation, there is an increasing need for safer, more inert gadolinium-based contrast agents, and for chelators that react rapidly with radiometals. Here we report the syntheses of a series of chiral DOTA chelators and their corresponding metal complexes and reveal properties that transcend the parent DOTA compound. We incorporated symmetrical chiral substituents around the tetraaza ring, imparting enhanced rigidity to the DOTA cavity, enabling control over the range of stereois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 60 publications
3
88
0
Order By: Relevance
“…Thus, the effect of chiral methyl pendant (L‐alanine vs. glycine) to the thermodynamic stability of the tris(aquated) Gd III complexes was realized and the effect of the chiral pendant was successfully established. Very recently, Caravan and co‐worker reported similar improvement in the stability of [Gd(DOTA)(OH 2 )] – complex by introducing chiral DOTA derivative as the ligands . Complex 1 afforded longitudinal relaxivity value of 10.95 m m –1 s –1 at 1.41 T, pH ≈ 7.4, and 25 °C.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, the effect of chiral methyl pendant (L‐alanine vs. glycine) to the thermodynamic stability of the tris(aquated) Gd III complexes was realized and the effect of the chiral pendant was successfully established. Very recently, Caravan and co‐worker reported similar improvement in the stability of [Gd(DOTA)(OH 2 )] – complex by introducing chiral DOTA derivative as the ligands . Complex 1 afforded longitudinal relaxivity value of 10.95 m m –1 s –1 at 1.41 T, pH ≈ 7.4, and 25 °C.…”
Section: Discussionmentioning
confidence: 86%
“… 11 For such reason, BFCs must display high thermodynamic stability and kinetic inertness toward the radionuclide to prevent dissociation and competition reactions (such as transmetalation by endogenous metals or transchelation by native ligands 9 , 12 ) but also allow mild and rapid labeling conditions, especially if the carrier moiety is a thermally sensitive biomolecule. 13 Moreover, BFCs not only coordinate the metal radionuclide, but they also modulate the pharmacokinetics of the resulting molecule.…”
Section: Introductionmentioning
confidence: 99%
“…This modification was inspired by the chiral DOTA derivatives recently proposed by Dai et al which have demonstrated higher stability and faster labeling properties with copper-64 and lutetium-177 compared to the DOTA analogues. 13 …”
Section: Introductionmentioning
confidence: 99%
“…The same is true of other chiral bio-active chemicals such as agrochemicals, pesticides and flavors. In recent years, researchers have also focused on the role of chirality in other areas such as catalysis [ 1 ], chiroptical applications [ 2 , 3 ], chiral magnetism [ 4 ], chiral semiconductors [ 5 ], cellular imaging [ 6 ], sensing [ 7 ], biomedical applications [ 8 ], chiral molecular assembly on surface [ 9 ], supramolecular chirality [ 10 ] and synthesis of chiral nanoparticles (NPs) [ 11 ]. One emerging field is chiral luminescent nanomaterials which have potential applications in chiral sensing [ 7 ].…”
Section: Introductionmentioning
confidence: 99%